Effect of Vaginal Cream with the Combination of Honey, Olive, and Propolis on the Symptoms of Uterine Cervicitis Symptoms in Women: A Double-Blind Randomized Controlled Clinical Trial Study - Hamideh Parsapour; Arezoo Shayan; Mehrnoosh Hosseinpoor; Seyedeh Zahra Masoumi; Farideh Kazemi; Shirin Moradkhani; Seyed Mohammad Hossein Oliaei; Zeinab Assareh; Mohammad Kazem Rashidi (Iranian Journal of Nursing and Midwifery Research)
Background: Uterine cervicitis in women requires careful selection of a suitable and straightforward treatment. This study aimed to examine the effect of Nika vaginal cream on the symptoms of uterine cervicitis in women. Materials and Methods: This double-blind, randomized, controlled clinical study was conducted on 66 women who where reffered to Hamadan health centers in 2021(33 people in each group). The participants in the intervention group were instructed to use Nika vaginal cream every night for 14 nights, along with a single dose of one gram of azithromycin, 400 mg of cefixime, and 500 mg of metronidazole twice a day for both the patient and her husband. The control group received a placebo cream and the same drugs as the intervention group. After the 14-day treatment period, clinical signs were assessed through examinations, and participants completed questionnaires again. Results: The study found that participants in the Nika user group experienced a 69.70% improvement in symptoms related to uterine cervicitis. This improvement was significantly higher than the control group, which only showed a 45.50% improvement. Although the Risk Ratio (RR) between the two groups was 53% higher in the intervention group, this difference was not statistically significant (p=0.06). However, the Risk Difference (RD) of 0.24 between the groups was found to be statistically significant (p=0.04). Additionally, participants in the intervention group reported a 76.00% reduction in dyspareunia (p=0.03) and an 84.00% reduction in urinary frequency (p=0.05). Conclusions: According to the result of RD, Nika vaginal cream had a significant effect on the improvement of cervicitis symptoms.